Problemas de la comprensión lectora en la educación rural - Romero Jiménez, Lourdes (2011)
Cultural diversity of Peru is a challenge, even more since an educational point of view, because cultural differences affect learning. Far such fact, children from rural areas have fewer possibilities to have access to an adequate education, considering the limitations of their environment and life conditions. lt is time to develop educational project with an authentic incorporation of variables able to change this situation